Fiscal and Economic Impact Analysis of Proposed Nexus Natural Gas Pipeline on the City of Green, Ohio: A Case Study. Issue 1 (1st November 2017) - Simons, Robert A.; Thomas, Andrew R.; Lendel, Iryna; Townley, Bryan
Abstract : In order to provide a sustainable outlet for natural gas harvested from the fracking fields of eastern Ohio, in 2015 Nexus announced plans to build 250 miles of high-pressure natural gas transmission pipeline that would run from the source into Michigan, ultimately to Ontario, Canada. The pipeline route passes through the fast-growing City of Green, Ohio, and could disrupt development plans there. The proposed path would cause the City of Green to disproportionately bear the burden of anticipated economic losses and reduction in tax revenue associated with the pipeline. Despite substantial front-loaded ad valorem taxes paid by the pipeline utility, over a 50-year period, the pipeline is projected to cause NPV fiscal losses of over $52 million, largely from foregone property and income taxes for future development.